Kegiatan Literasi Dasar Dan Minat Baca Siswa SD Kelas Rendah - Shelty D.M. Sumual; Paulus R. Tuerah; Yudi B. Londa; Marlina Terok; Marlina Manimbage (Peneliti.net, 2023)
The aim of this research was to obtain information about basic literacy activities and reading interest of low grade elementary school students. This research is a research using literature study method or literature review. Teaching reading or the school literacy movement is not only expected to be able to improve reading skills, but also to increase students' interest in reading. Increasing interest and fondness for reading will have a positive effect on students' attitudes when reading. Students who have an interest in reading will also try to improve their reading skills and vice versa.